Pelatihan Pengolahan Bawang Merah dengan Alat Pebmo Pada Kelompok Petani Bawang Merah Di Desa Sekoto Kabupaten Kediri - Indrawati, Elsanda Merita; Munawi, Hisbullah Ahlis; Suwardono, Agus; Santoso, Rachmad; Manikta, M. Dewi; Mahdiyah, Umi; Nadliroh, Kuni; Nevita, Ary Permatadeny (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Sekoto Village is the largest onion producer center in Kediri Regency. The aim of this service activity is to provide training on processing low quality shallots into high quality fried onion products using an Automatic Shallot Processing Machine (PEBMO) that is practical, effective and efficient. The activity material provided was about the marketing of shallots and the processing of low quality shallots starting from stripping of shallots, chopping onions, and draining oil using an Automatic Shallot Processing Machine (PEBMO). Community service activities (PKM) which include (1) observation; (2) design and provision of tools (PEBMO) to shallot farmers; (3) socialization; (4) training and practice; (5) monitoring. This activity is useful to increase the income of shallot farmers, this is because low quality shallots are processed into high-quality fried onion products with a stable selling price, so that shallot farmers will not lose if the yields produced have low quality.